Contribution to the study of cardiovascular autonomic nervous system in relation to life in the highlands - Cabieses Molina, Fernando (1946)
The study of the Cardiovascular System Neurovegetative Andino, is a worthy subject of a lengthy investigation, as has peculiar complexities that apparently put him on the sidelines of the facts commonly observed in Physiology sea level. The secret of adaptation to life at high altitude is, in our opinion, in the field of Neuro-endocrinology, and in the process not only play important role mechanisms for better utilization of atmospheric oxygen, but the mechanisms to prevent acapnia, which is easily reached by the exaltation of the first. One of the things that has drawn attention in the operation of the Andean Cardiovascular Neurovegetative is the post-effort, bradycardia upon which various concepts have been issued without definitive conclusions. The action-sensitive glass on the heart rate zones appears to play an important role in the development of this phenomenon.